Waste Management Strategy In Central Aceh Regency, Aceh Province - Maulana Maulana; Muh Ilham; Sutiyo Sutiyo (Sean Institute, 2024)
The phenomenon of rejection of waste being disposed of at the Uwer Tetemi landfill, which causes waste not to be managed and handled, resulting in the accumulation of waste around the city and the surrounding community which is dominated by household waste and similar types of household waste, which often occurs in Central Aceh Regency, which is a problem in research this time. The aim of this research is to find out how waste is managed in Central Aceh Regency and to formulate appropriate waste management strategies at the Central Aceh Regency Environmental Service, Aceh Province based on SOAR analysis. This research uses descriptive qualitative methods. This research analyzes waste management using waste management subsystem components by Damanhuri and Padmi (2010) and uses SOAR analysis by JM Stavros and Cole (2014) in describing SOAR factors in the organizational environment. Data collection techniques in this research used observation, interviews, documentation, and Focus Group Discussion (FGD) techniques. Researchers use data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. In testing the validity of the data, researchers used source triangulation. The results of the research show that the waste management system in Central Aceh Regency consists of regulations related to waste management based on Qanun Number 1 of 2018 concerning Waste Management and Regent's Regulation Number 51 of 2018 concerning Policies and Strategies for Management of Household Waste and Similar Types of Household Waste, management implementation waste is carried out by DLH Central Aceh Regency, operational techniques for waste management are not fully in accordance with regulations and SOPs, APBD is the largest source of funds assisted by cleanliness levy funds, the level of community awareness is still low because facilities and infrastructure are inadequate in the village environment. Researchers suggest that the Central Aceh District Environmental Service consider implementing this movement from six main strategies to support waste management activities in Central Aceh District.